Association Between the STAD Cooperative Learning Model and Students’ Interpersonal Intelligence in Islamic Religious Education - Aprizal; Dian Namora; Wan Shariza Wan Zainal Abidin (CV Najmi Edu Creative, 2026)
This study examined the relationship between the Student Teams Achievement Division (STAD) cooperative learning model and students’ interpersonal intelligence in Islamic Religious Education. The study applied a quantitative correlational design involving 70 seventh-grade students at a public junior high school in Indonesia. Data were collected using Likert-scale questionnaires measuring the implementation of the STAD cooperative learning model and students’ interpersonal intelligence. The instruments were tested for validity and reliability prior to data collection. Data analysis was carried out using descriptive statistics, normality testing, and simple linear regression through SPSS 22. The findings indicated that both the implementation of the STAD cooperative learning model and students’ interpersonal intelligence were categorized at high levels. Regression analysis demonstrated a significant positive relationship between the STAD cooperative learning model and students’ interpersonal intelligence (p < .05), with the model explaining 51.4% of the variance in interpersonal intelligence scores (R² = .514; R = .717). These results indicate that cooperative learning practices accentuating collaboration, communication, and peer interaction are associated with stronger interpersonal competencies among students in Islamic Religious Education contexts.